Clinical Care of Victims of Interpersonal Violence and Rape in Tanzania: A Qualitative Investigation - Mgopa LR; Rosser BRS; Ross MW; Mohammed I; Lukumay GG; Massae AF; Mushy SE; Mwakawanga DL; Mkonyi E; Trent M; Bonilla ZE; Wadley J; et al. (Dove Medical Press, 2021)
Lucy R Mgopa,1 B R Simon Rosser,2 Michael W Ross,3 Inari Mohammed,2 Gift Gadiel Lukumay,4 Agnes F Massae,4 Stella E Mushy,4 Dorkasi L Mwakawanga,4 Ever Mkonyi,2 Maria Trent,5 Zobeida E Bonilla,2 James Wadley,6 Sebalda Leshabari4, † 1Department of Psychiatry and Mental Health, School of Medicine, Muhimbili University of Health and Allied Sciences (MUHAS), Dar Es Salaam, Tanzania; 2Department of Epidemiology and Community Health, School of Public Health, University of Minnesota, Minneapolis, MN, USA; 3Program in Human Sexuality, Department of Family Medicine, University of Minnesota, Minneapolis, MN, USA; 4Department of Community Health Nursing, School of Nursing, Muhimbili University of Health and Allied Sciences, Dar Es Salaam, Tanzania; 5Department of Adolescent and Young Adult Medicine, Johns Hopkins University Schools of Medicine and Public Health, Baltimore, MD, USA; 6Department of Counseling and Health Services, Lincoln University, Philadelphia, PA, USA†Dr. Leshabari passed away on October 16th, 2020.Correspondence: B R Simon RosserUniversity of Minnesota, 1300 S. 2 nd St. #300, Minneapolis, 55454, MN Tel +1 612- 624-0358Email rosser@umn.eduIntroduction: Africa has high rates of interpersonal violence and rape, although little is known about how these cases are handled in the clinical setting.Methods: We enrolled 121 health care professionals and students in Tanzania from the fields of midwifery, nursing and medicine, and conducted 18 focus group discussions stratified by both professional and clinical experience. Two clinical scenarios were presented across all groups and participants were asked to give their opinions on how the hospital they worked in would manage the cases. Case 1 focused on how to address a case of an injured woman beaten by her husband (and whether the perpetrator would be reported to the police). Case 2 focused on how to handle a rape victim who is brought to the hospital by the police.Results: Participants considered both cases as emergencies. There was a similarity in the clinical care procedures across both scenarios. This included building rapport with the patient, prioritization of the medical care, history taking, and referring to other specialties for follow-up. Participants differed in how they would handle the legal aspects of both cases, including whether and how to best follow mandated reporting policies. Providers wondered if they should report the husband in case study 1, the criteria for reporting, and where to report. Providers displayed a lack of knowledge about resources needed for sexual violence victim and the availability of resources.Conclusion: These findings indicate that cases of intimate partner violence and rape are likely to be under-reported within hospitals and clinics in Tanzania. Health care providers lack training in their required obligations and procedures that need to be followed to ensure victim's safety. The findings confirm that there is a need for health care students in Tanzania (and possibly Africa) to receive comprehensive training in how to handle such cases.Keywords: IPV, violence, rape, GBV, health provider, Tanzania